THE EFFECTIVENESS OF ZAKAT FUNDING THROUGH DOMPET DHUAFA BEASTUDI ETOS SCHOLARSHIP PROGRAM - Srinovita, Yulya; Udiutomo, Purwa; Haryadi, Pedri (Journal of Islamic Monetary Economics and Finance, 2016)
The Problems of education and poverty are interrelated. The poor people cannot access higher education and they will remain poor with insufficient education. Therefore, the effort to break the cycles of poverty is to provide opportunities for the poor to obtain higher education Dompet Dhuafa through Beastudi Etos empowers education by providing coaching, mentoring and education financing funding. The population of this research is all of the beneficiaries alumni Beastudi Etos scholarship with a total sample of 190 respondents. The result of the research has shown that Beastudi Etos scholarship program is one of the programs that are quite effective in breaking the cycles of poverty through education and economic improvement. The result also indicates that the program is effective in creating excellent and independent generation. It is shown that 81.58% of respondents have successfully completed their studies (Bachelor, Master and Doctoral degrees), the others are in the process of finishing bachelor degree. 88.95% of the respondents have worked and earn income more than 7,000,000 Rupiah/month, 21.5% have dependents from 1 up to 13 persons. In general, the respondents state that coaching and mentoring which has been given is affected on the character (97.4%), skills (94.2%), socials skill (97.9%), and social generosity (97.9%).